Effects of Relationship Marketing on Customer Loyalty: Study of Commercial Banks of Sindh - Jamil, Shabana; Saleh Memon, Muhammad; Ahmed Soomro, Mansoor (International Journal of Psychosocial Rehabilitation, 2020)
Loyalty is the debatable issue of every manufacturing and service-oriented organization due to healthy competition. Nowadays, every owner of the business wants their business safe because their survival is at stake for coping with this issue. Every organization is working for loyalty in their customers. In this regard, the study was carried out to predict customer loyalty by creating different concepts and relationship-marketing variables: trust, commitment, communication, conflict management, bonding, and satisfaction to correctly predict customer loyalty and the gap. The study focused on the service sector (commercial banks) of Sindh province through a structured questionnaire, and a pilot study was conducted based on 50 responses. Then, after 500 questionnaires were distributed for getting a response from account holders of different banks, the data was entered in SPSS-18 for checking the reliability of scale again. The data reduction method was used by looking at the assumption of MSA. Chisquare significance, eigenvalue of the component was checked, the collinearity issue was also checked by checking the correlation between independent variables, and finally linear regression was applied to check the hypothesis. Moreover, the study concluded that trust, communication, conflict management, and bonding variables are positively and significantly contributing to customer loyalty, commitment, and satisfaction has no concern with customer loyalty in commercial banks of Sindh, but the fitness of model is critical because error term is too large; hence, more research is needed to predict customer loyalty correctly for commercial banks.